Características asociadas a la evolución clínica de pacientes hemodializados por enfermedad renal crónica Hospital Regional de Loreto 2018-2019, Iquitos 2023 - Vasquez Sandoval, Luis Joseph (2024)
The objective of the research was to determine the characteristics associated with the clinical evolution of patients undergoing hemodialysis for chronic kidney disease Hospital Regional de Loreto 2018-2019 Iquitos 2023. The method was quantitative, non-experimental, correlational, retrospective design. The population and sample consisted of 90 medical records of patients undergoing hemodialysis for chronic kidney disease. The technique used was documentary analysis and the instrument was a record sheet of characteristics and clinical evolution of patients undergoing hemodialysis for chronic kidney disease. The data were analyzed with SPSS 24.0 and the chi square test (X2) for bivariate analysis. The results indicated that 64.4% patients were between 30 and 59 years old, 50.0% were men, 44.7% had maintained independence, 28.9% had diabetes, 39.0% had a disease of 1 at 3 years and 48.1% were on hemodialysis for more than 1 year. In relation to the clinical evolution, 54.6% improved, 28.9% remained stable, 8.8% worsened and 7.7% died. In conclusion, an association was confirmed between the clinical evolution on hemodialysis due to comorbid chronic kidney disease (p=0.016), and hemodialysis time (p=0.001). No associations were found with age (p=0.295), sex (p=0.737) and occupation (p=0.195) and duration of illness (p=0.116).